Beastly Spirits: A Pack of Folks. Issue 3 (1st October 2016) - Oleynikov, Nikolay; Timofeeva, Oxana
Abstract : Nikolay Oleynikov and Oxana Timofeeva are members of the Saint Petersburg–based collective Chto Delat, a group of nondogmatic Marxist artists, philosophers, and activists. Members of the group are in continuous interdisciplinary dialog. This artwork is an example of the circulation of ideas, images, and practices that flow from the members of the collective, influencing the singular studies of each artist, and back from the singular exercises of each artist, enriching the practices of the collective. Combining the images of Oleynikov and a text by Timofeeva, the artwork analyzes a collective dimension of spirituality that through artistic political practices uncovers a series of transformations of animal bodies, addressing the nonhuman aspects of the phenomenon of comradeship. In this uncovering, questions of solidarity, pain, and utopian community are raised and actualized in the encounter between text and image.